CHROMATIC DISPERSION IN OPTICAL COMMUNICATIONS (Perner's Contacts, 2012)
This article deals with chromatic dispersion causes in optical fibres and with its effects on signal transmission. The ways of dispersion compensation are described and illustrated through simulations OptSim software.
Keywords: Chromatic dispersion, DCF, MMSF, OptSim, Bragg grating (FBR), eye diagram